Extraction of Phenol Compounds in the Liquid Smoke by Pyrolysis of Oil Palm Fronds - Seri Maulina; Nurtahara (Jurnal Inovasi Teknologi, 2020)
The total content of phenol compounds present in the liquid smoke can be extracted either by using polar or non-polar solvents. Polar and non-polarsolvents are often used to extract phenol compounds from plants. Extraction of phenol compounds was performed by using ethyl acetate and hexanesolvents at 40° C, 55° C and 70° C within 60, 120, and 180 minutes. The highest total content of phenol compounds is obtained through extractionprocess at 70o C within 180 minutes using ethyl acetate solvent, which is 103,394 mg/g. While, the lowest one is obtained through extraction processat 40o C within 60 minutes using hexane solvent, which is 13,697 mg/g. The phenol compounds obtained are syringol and guiaicol compoundsusing ethyl acetate solvent within 180 minutes, at the temperature of 70o C, which is 5,44% and 3,97%.